The Influence of Perceived Organizational Support and Transformational Leadership on Readiness for Change: The Mediation Role of Organizational Trust (Study on the Financial Administration Unit) - Marnoto, Kurnia Yudo; Desiana, Putri Mega (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The government plans to move the country's capital from Jakarta to the Archipelago Capital (IKN) in East Kalimantan. This has become a hot topic for research, including research on the impact and risks of transferring IKN to civil servants (PNS) who are transferred to IKN. This study highlights the level of individual readiness in facing the transfer of civil servants to IKN by evaluating the influence of perceived organizational support, transformational leadership, and organizational trust on individual readiness to change. Quantitative research methods through self-administered questionnaires were carried out on 311 employee respondents in the Financial Administration Unit. Hypothesis testing uses the Structural Equation Model with Lisrel 8.8. The research results show that perceived organizational support and transformational leadership have a significant positive effect on readiness for change. Furthermore, organizational trust partially mediates the relationship between perceived organizational support transformational leadership, and readiness for change. This research contributes to the field of human resource management through practical guidance for increasing readiness for change in the context of organizational change, especially the transfer of employees to the Indonesian capital, in public sector organizations.